2019
DOI: 10.3390/met9080912
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Laser Remelting on the Microstructure and Performance of Bainitic Steel

Abstract: The surface of bainitic steel was remelted by fiber laser, and the microstructure and mechanical properties of the melted layer were studied by scanning electron microscopy (SEM), transmission electron microscopy (TEM), a nanoindentation instrument, and wear equipment. The study of changing the laser scanning speed showed that the depth of the melted layer increases with decreases of the laser scanning speed. The wear-resistance property increased by 55% compared with the matrix and decreased with the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Wang [24] studied the cracking mechanism of TiAl alloy prepared by SLM (Selective Laser Melting) method, and put forward a new strategy to eliminate cracks. The research revealed that laser remelting results in the material acquiring a refined and uniform grain structure, devoid of cracks and pores, thereby exhibiting enhanced strength and wear resistance [25]. The application of laser surface remelting on H21 steel has been found to effectively reduce both the size and density of cracks [26].…”
Section: Introductionmentioning
confidence: 99%
“…Wang [24] studied the cracking mechanism of TiAl alloy prepared by SLM (Selective Laser Melting) method, and put forward a new strategy to eliminate cracks. The research revealed that laser remelting results in the material acquiring a refined and uniform grain structure, devoid of cracks and pores, thereby exhibiting enhanced strength and wear resistance [25]. The application of laser surface remelting on H21 steel has been found to effectively reduce both the size and density of cracks [26].…”
Section: Introductionmentioning
confidence: 99%
“…Laser remelting (LR) is similar to the LC process, and the difference between the two is that LR only produces laser and does not add any additional material. LR [12,13] can not only improve the surface quality of the substrate or coating but also make certain changes in the macroscopic morphology and microstructural composition of the material surface layer [14,15] and reduce or eliminate defects such as cracks and porosity within the coating [16]. It effectively improves the performance of the original workpiece in service [17] and increases the lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the region is quickly solidified via heat conduction from the substrate, so the obtained microstructure is different from the matrix, and when the selected laser processing parameters are appropriate, the grain will be refined. The material's hardness is also much improved based on the pattern [16][17][18]. In this way, the non-smooth bionic structure with soft and hard phases is processed on the surface.…”
Section: Introductionmentioning
confidence: 99%